Mapping the intellectual structure and landscape of colorectal cancer immunotherapy: A bibliometric analysis - Qin Ling Ou; Yong Long Chang; Jin Hui Liu; Hai Xia Yan; Lin Zi Chen; Duan Yang Guo; Si Fang Zhang (Taylor & Francis Group, 2024)
ABSTRACTImmunotherapy, particularly immune checkpoint inhibitor (ICIs) therapy, stands as an innovative therapeutic approach currently garnering substantial attention in cancer treatment. It has become a focal point of numerous studies, showcasing significant potential in treating malignancies, including lung cancer and melanoma. The objective of this research is to analyze publications regarding immunotherapy for colorectal cancer (CRC), investigating their attributes and identifying the current areas of interest and cutting-edge advancements. We took into account the publications from 2002 to 2022 included in the Web of Science Core Collection. Bibliometric analysis and visualization were conducted using CiteSpace, VOSviewer, R-bibliometrix, and Microsoft Excel. The quantity of publications associated with this domain has been steadily rising over the years, encompassing 3753 articles and 1498 reviews originating from 573 countries and regions, involving 19,166 institutions, 1011 journals, and 32,301 authors. In this field, China, the United States, and Italy are the main countries that come forward for publishing. The journal with the greatest impact factor is CA-A Cancer Journal for Clinicians. Romain Cohen leads in the number of publications, while Le Dt stands out as the most influential author. The immune microenvironment and immune infiltration are emerging as key hotspots and future research directions in this domain. This research carries out an extensive bibliometric examination of immunotherapy for colorectal cancer, aiding researchers in understanding current focal points, investigating possible avenues for research, and recognizing forthcoming development trends.